Experimental Study on Flexural Behaviour of Reinforced Foamed Concrete Square Hollow Beam - Rokiah, Othman; Khairunisa, Muthusamy; Putra Jaya, Ramadhansyah; Duraisamy, Youventharan; M. A., Sulaiman; Nadiatul Adilah, Ahmad Abdul Ghani; Chong, B. W. (IOP Publishing, 2020)
Nowadays construction industry continuously looking for new, better and efficient construction material and method due to environmental impact. This research reported the effect of reinforced foamed concrete square hollow beam in order to reduce the effect of the application of concrete materials. Foamed concrete with density of 1600kg/m³ is now widely used as a structural component like slab and wall due to it lighter than the normal concrete. Meantime, it helps in saving cost and reduce the use of formwork. The hollow section also can reduce the dead loads which contribute to seismic effect in high rise buildings. In addition, the Processed Spent Bleaching Earth (PSBE) is an industry waste which possess a good pozzolanic reaction is used as partial cement replacement in order to make it more environmentally friendly. The experimental program consists of casting and testing of foamed concrete beams of size 150 x 200 x 1500 mm with and without square hollow section. To study the flexural behaviour, all beams are tested after 28 days of curing subjected to four-points bending test in order to analyse the effect of the reinforcement of hollow section on the strength, deflection and mode of failure of foamed concrete beam. The performance of reinforced foamed concrete hollow square beam (RHB) under flexural shows better when compared with conventional solid beam (CSB) and hollow square beam without reinforcement (HB). The RHB exhibited greater strength with lesser deflection and cracking.